MODIFIKASI TAMBATAN PERAHU UNTUK ARMADA TUNA SKALA KECIL DI DUSUN PARIGI DESA WAHAI SERAM UTARA - Ruslan H. S. Tawari; Taufiniringsi Kesaulya; Rahmawati Muna (Universitas Pattimura, 2022)
Boat mooring is a place for tying/tethering boats while anchoring/parking before and after loading and unloading cargo (goods and people), Boat moorings are part of what complements other buildings such as fish auction sites, fishing village neighborhoods, (BPS 2020). This study aims to analyze the size and structure of boat mooring construction as well as the operating mechanism of boat moorings in small-scale tuna catching businesses in Parigi Wahai Village. This research was conducted in Parigi Wahai village for 2 (two) months, from February to March 2019. This research was conducted using observation and interview methods, (Arikunto 2010). Primary data collection is done by purposive sampling,. Data analysis was carried out in a qualitative descriptive, The results showed that the construction of the boat moorings in Parigi Wahai village, was a combination of a truss bridge and a suspension bridge at the rear of the mooring. The operation of the mooring of the boat, is carried out by directing the boat into the mooring pool, with the stern of the boat facing the sea then installing a sling rope on the boat, then the process of lifting the boat using pulleys and rollers until the boat is placed on the retaining beam.